The Traveling Wave Solutions of Date–Jimbo–Kashiwara–Miwa Equation with Conformable Derivative Dependent on Time Parameter - Akturk, Tolga; Alkan, Aslı; Bulut, Hasan; Güllüoğlu, Nesrin (My University, 2024)
In the paper, the traveling wave solutions of the conformable derivative Date–Jimbo–Kashiwara–Miwa equation were obtained by the modified exponential function method (MEFM). It has been seen that the wave solutions found are functions that have the feature of being periodic functions. The proper values for the parameters in the acquired wave solutions are then used to generate two contour and density graphs in three dimensions that simulate the solution functions.
Keywords: Traveling wave solution; modified exponential function method; Conformable Date–Jimbo–Kashiwara–Miwa equation